PENGARUH MEDIA SOSIAL FACEBOOK TERHADAP KARAKTER DISIPLIN PESERTA DIDIK KELAS X DI SMK NEGERI 4 SELAYAR - Bakhtiar, Bakhtiar; Agus, Andi Aco; SARI, NITA (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
The Influence of Facebook Social Media on the Disciplinary Character of Class X Students at SMK Negeri 4 Selayar. Thesis. Study program Pancasila and Citizenship Education, Civics Law Department Makassar State University Faculty of Social Sciences and Law. Supervisor Bakhtiar and supervisor II Andi Aco Agus. This research aims to: 1). Knowing the use of Facebook of class X students at SMK Negeri 4 Selayar. 2). Knowing the character of class X students at SMK Negeri 4 Selayar. 3). To find out whether there is a significant influence between the use of Facebook on the character formation of class X students at SMK Negeri 4 Selayar. The research method used in this research is method quantitative with two variables, namely social media Facebook as a variable free (independent variable) and discipline character as the dependent variable (dependent variable). With data collection techniques using questionnaires and instruments used in this research. In data analysis techniques, researchers use descriptive statistical analysis and inferential statistical analysis. The sample was 76 students from a population of 76 students, the sampling technique used Total Sampling. Based on the results of research and data analysis carried out by researchers, it can be concluded that the results of collecting research data from 76 students who were given questionnaires were then tested using a simple linear regression formula, obtained a = 46.584, b = 0.026 so that Y = 46.58+0.026 X . The use of social media Facebook influences the discipline character of students. Using the product moment correlation test with a significance level of 5%, the results obtained show that the calculated r value is greater than the table r value. Because r calculated > r table = 0.831 < 0.227 then Ho is rejected and Ha is accepted. This shows that there is an influence of the use of social media Facebook on the discipline character of class X students at SMK Negeri 4 Selayar. Furthermore, the results of calculating the contribution of variable This means that the student's discipline character value is 0.69% determined by the social media Facebook. The remaining 0.31% is determined by other variables.